Chemotherapy Training Model To Improve Nurse Competence In The New Life Order Era - Srioetari S, Poetri (Riviera Publishing, 2022)
Introduction: Chemotherapy is one of treatments given to cancer patient which may cause potentially fatal side effect, death. Chemotherapy treatment is provided in an area with staffs trained in giving service based on the guidelines for treatment, preventing side effect and implication of the chemotherapy. The occurrence of Covid-19 pandemic requires the community to apply the new life order, including causing training as a learning process to have adjustment. This qualitative research aimed at examining the chemotherapy training model which may be implemented to nurses to improve their competence in the new life order situation and condition. Method: Focus Group Discussion was carried out with the executing nurses who had participated in chemotherapy training before the Covid-19 pandemic and in-depth interview was carried out with hospital medical staffs and room leader of oncological service room at the Hospital, and partner doctors. The results of FGD and interview were analyzed by summarizing, categorizing and making themes, designing them into a chemotherapy training model as needed by nurses to improve their competence. Result and Discussion: The materials and theories of chemotherapy training were delivered on an electronic based. The skill materials should, otherwise, be delivered face-to-face. The nurses stated that direct learning in service site made it easier for them to understand the materials. Learning was carried out in small groups through role play, and mentoring/coaching was also a learning method that was necessarily taken into consideration. Conclusion: Face-to-face method improved the competence better, but with the Covid-19 pandemic situation, of which end was yet unknown, and the new life order condition, the training model built should keep considering the health and safety of patients, health workers and training participants